Colour image encryption and decryption using arnold’s cat map and Henon map - Siti Nurul Hatikah Mohammad; Arif Mandangan (Semarak Ilmu, 2024)
Image encryption plays a crucial role in securing sensitive visual information during transmission and storage. Throughout the encryption and decryption phases of images, the utilized ciphers exhibit substandard quality, resulting in the persistence of the original image. Consequently, the issues at hand stem from a deficiency in the quality of cipher image, thereby compromising the confidentiality level to an unsafe extent. This research explores the application of chaotic maps, specifically the Arnold Cat Map and Henon Map for the encryption and decryption of digital colour images. The encryption process involves applying the Arnold Cat Map and Henon Map to permute and diffuse pixel values, enhancing the confusion and diffusion properties essential for robust encryption. The study provides insights into the decryption efficiency and the ability to recover the original image from the ciphered version. This research contributes to the body of knowledge in colour image encryption techniques and offers a novel approach leveraging chaotic maps. The findings emphasize the importance of selecting suitable chaotic maps and their parameters to achieve a balance between security and image quality.